Cultural Literacy Training: Maintaining the Value of Harmonizing Local Culture amidst the Onslaught of Foreign Culture - Agus Santoso, Aris Prio; Winarti, Winarti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This community service will be carried out regionally in Hargobinangun Village (Jl. Kaliurang KM. 20 Sawungan, Hargobinangun, Pakem, Sleman, Yogyakarta). The targets of this Community Service are traditional, religious leaders, Small and Medium Business actors and also the community who manage tourism in Hargobinangun Village. The aim of this community service is to train the community to increase the speed of the process of increasing human resource capabilities towards cultural literacy in accordance with the rate of growth development. The method used in this service is a literal approach, namely an action plan consisting of a set of steps to solve a problem or achieve a goal, then a mental procedure in the form of a sequence of steps that uses creative efforts to achieve a certain goal. This community service is planned to be carried out within 2 months after obtaining approval from the Educational Institution and Partners. Based on the results of Community Service, data was obtained that young people in Hargobinangun Village have participated in foreign cultures. Ways to maintain local culture amidst the onslaught of foreign culture include: using social media, educating parents, all village activities involving young people, and innovating food products originating from foreign countries into local food products that still maintain their philosophy. After the activity was carried out, it showed that 20 participants had understood the training material provided. However, to apply the material in everyday life, only 75% are able to apply it. One of the reasons is the lack of capital when innovating existing Jadah and the need for tools that are deemed inadequate. As many as 75% of participants have started marketing innovative products as an implementation of harmonized values amidst the onslaught of foreign culture.